PENINGKATAN KINERJA GURU DALAM PEMBELAJARAN DI KELAS MELALUI SUPERVISI AKADEMIK DI SMP NEGERI 3 KUALA MANDOR B - Damanik, Karim (Jurnal Pembelajaran Prospektif, 2020)
This research is a School Action Research. The subjects of this study were the teachers who taught at SMP Negeri 3 Kuala Mandor B. This research took place in 2 cycles. Each cycle consists of one meeting, Data collection techniques using observation, and documentation. The type of data collected is observational data on teacher learning outcomes in class. The School action research conducted in these two cycles is considered successful if there is an increase in teacher performance reaching 85% of teachers who have achieved mastery with an average grade of 75. Based on the results of the study, improving teacher performance in the learning process, through coaching Academic supervision the results are very good. This was evident at the first meeting of the 5 teachers who were present at the time of the study the average grade reached; 65.50% increased to 83.75%. From the analysis of the data above, teacher development by the school principal through Academic supervision is effectively implementedin an effort to improve teacher performance achievements, which means that the process of developing school principals is more successful and can improve teacher performance in the learning process, particularly SMP Negeri 3 Kuala Mandor B, Kubu Raya Regency. It is therefore expected that principals can carry out coaching through ongoing academic supervision.